Insights into the active surface species formed onTa2O5nanotubes in the catalytic oxidation of CO - Gonçalves, Renato V. (2014)
Freestanding Ta2O5nanotubes were prepared by an anodizing method. As-anodized amorphousnanotubes were calcined at high temperature to obtain a crystalline phase. All materials were studied bymeans of BET analysis, XRD, TEM, SEM, XPS, and FTIR and were evaluated in the catalytic oxidation ofCO. An XPS study confirmed the formation of different tantalum surface species after high temperaturetreatment of amorphous Ta2O5nanotubes. Calcination at 8001C generated Ta4+while highertemperature (10001C) treatment led to the formation of Ta3+species. These materials also showedsignificant differences in catalytic activity. Higher activity was observed for samples calcined at 8001Cthan at 10001C, suggesting that Ta4+species are active sites for CO oxidation.